Predictors of Malnutrition among Children Aged 6-59 Months Attending Maternal Child Health Clinic at Ekerenyo Sub-County Hospital in Nyamira County (Global Journal of Medical Research, 2021)
Malnutrition is the cellular imbalance between supply of nutrients and energy and the body#x2019;s demand for them to ensure growth, maintenance and specific functions. Malnutrition affects a great number of children globally with 99million underweight and 51million wasted hence remains a public health concern. Prevalence of child malnutrition in Kenya is high with stunting (26.0%), wasting (4.0%) and underweight (11.0%) among children under-five years. The general objective is to determine the predictors of malnutrition among children aged 6-59 months attending maternal child health clinic at Ekerenyo Sub-County hospital in Nyamira County.